FRANZ KAFKA AND STEFAN ZWEIG IN AZERBAIJAN RESEARCH AND TRANSLATIONS - Kheyri, Al-Abbasi Noval (International Journal of Psychosocial Rehabilitation, 2020)
The well-known Austrian writers Kafka and Zweig, as in all the world, are popular in Azerbaijan also. Since 1960s their works have been repeatedly translated and analyzed by Azerbaijan literature scholars. In the article all these literary facts are investigated and are shown as a significant aspect of Azerbaijan-Austria literary relations. The research work indicates that the majority of poets and writers of the XX century Austria, of course, does not try to reflect abstract ideas, on the contrary, create certain methods of exiting from extreme situation. Although, the philosophy of the authors and their literary characters are quite subjective, and sometimes are presented as an abstract and a passive lifestyle, a certain pattern (or stereotype) of the nostalgic behavior has emerged.